2010
DOI: 10.1021/la101131v
|View full text |Cite
|
Sign up to set email alerts
|

Dilational Properties of Anionic Gemini Surfactants with Polyoxyethylene Spacers at Water−Air and Water−Decane Interfaces

Abstract: The dilational properties of anionic gemini surfactants (oligooxa)-alpha,omega-bis(m-octylbenzene sulfonate) (C(8)E(x)C(8)) with polyoxyethylene spacers at the water-air and water-decane interfaces were investigated via the oscillating barriers method. The influences of oscillating frequency and bulk concentration on dilational properties were explored. The interfacial tension relaxation method was employed to obtain dilational parameters in a reasonably broad frequency range. The experimental results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…A considerable number of investigations have been reported on the surface activity and aggregation behaviors of gemini surfactants. Usually a longer hydrophobic chain leads to higher surface activity (lower CMC), but some unexpected results have been found that contradict the typical monotonic ''longer'' to ''higher'' change [40,41]. Among these aberrant properties, one noteworthy phenomenon is that the CMC of some gemini surfactants increases when the chain length of the alkyl hydrophobic group goes beyond a critical length.…”
Section: Greenolution Of Industrial Needs By Using Cationic Geminismentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable number of investigations have been reported on the surface activity and aggregation behaviors of gemini surfactants. Usually a longer hydrophobic chain leads to higher surface activity (lower CMC), but some unexpected results have been found that contradict the typical monotonic ''longer'' to ''higher'' change [40,41]. Among these aberrant properties, one noteworthy phenomenon is that the CMC of some gemini surfactants increases when the chain length of the alkyl hydrophobic group goes beyond a critical length.…”
Section: Greenolution Of Industrial Needs By Using Cationic Geminismentioning
confidence: 99%
“…Among these aberrant properties, one noteworthy phenomenon is that the CMC of some gemini surfactants increases when the chain length of the alkyl hydrophobic group goes beyond a critical length. Thus, studies of the relationship between gemini structure and property are important, not only theoretically, but also from the practical stand point [41].…”
Section: Greenolution Of Industrial Needs By Using Cationic Geminismentioning
confidence: 99%
“…For both curves, there were two maxima at lower frequencies, which admit the occurrence of multiple relaxation processes owing to the longer time intervals between external disturbances. In fact, such dilatational behaviour has been discovered for some nonionic surfactants [37] and a Gemini surfactant with an ethylene oxide chain as the spacer [25]. The reason is attributed to the reorientation and compression of ethylene oxide chains in the interfacial layer [25]; however, the Gemini surfactant 12(2OH)-8-12(2OH) does not have a long ethylene oxide chain as either a hydrophilic head group or spacer; the explanation above may not be suitable.…”
Section: Influence Of Concentrationsmentioning
confidence: 98%
“…In fact, such dilatational behaviour has been discovered for some nonionic surfactants [37] and a Gemini surfactant with an ethylene oxide chain as the spacer [25]. The reason is attributed to the reorientation and compression of ethylene oxide chains in the interfacial layer [25]; however, the Gemini surfactant 12(2OH)-8-12(2OH) does not have a long ethylene oxide chain as either a hydrophilic head group or spacer; the explanation above may not be suitable. Zana et al investigated the adsorption behaviour of alkanediyl-α,ω-bis(dimethylalkylammonium bromide) Gemini surfactants at an air/water interface [38].…”
Section: Influence Of Concentrationsmentioning
confidence: 98%
See 1 more Smart Citation